Biochemical Studies on Bio Extracts as Antioxidant and Antibacterial Activity - M, Farid; Ali, Hanaa F. M; Massoud, Gehan F. A; Abdelmagayed, Sherein Saleh (Journal of agricultural, environmental and veterinary sciences, 2017)
Biochemical Evaluated of some bio extracts as follows: Chemical composition and Phytochemical screening were determined in Tilia Cordata and Vitex Agnus leaves. The total polyphenols and flavonoids contents of Tilia Cordata leaves have the highest of total polyphenols and flavonoids contents, which were 126.00mgGAE/g and 15.88mgQE/g, followed by Vitex Agnus leaves, which were 119.77mgGAE/g and 13.41mgQE/g, respectively. Methanolic and aqueous extracts of plants leaves were antioxidant activity by used (FRAP, LPO, DPPH and ABTS) The methanolic extract of Tilia Cordata and Vitex Agnus  leaves, have the highest of reducing power which were 1.649 and 1.018 at the concentrations of 80mg/ml, respectively. Also, by used (LPO, DPPH and ABTS), were the highest antioxidants activity for methanolic extract respectively. Moreover, the methanolic extract of Tilia Cordata leaves produced the highest growth inhibition (18 and 17mm) for against Escherichia coli and Bacillus subtillis at 4mg/ml, respectively. While, The methanolic extract of Vitex Agnus produced the medium percentage of growth inhibition (10.5, 9.75 and 10mm) for against Escherichia coli, St.coccus aureus and Bacillus subtillis at 4mg/ml, respectively. And compared with antibiotic. This study concluded that Tilia Cordata and Vitex Agnus  leaves extract has an antioxidant and antibacterial activity.
Keywords: Chemical composition; Phytochemical; Antioxidant and Antibacterial activity